Linear Angiosperm Phylogeny Group (LAPG) III: a linear sequence of the families in APG III - HASTON, ELSPETH; RICHARDSON, JAMES E; STEVENS, PETER F; CHASE, MARK W; HARRIS, DAVID J (Botanical journal of the Linnean Society, 2009)
The publication of the third Angiosperm Phylogeny Group (APG) classification (APG III. 2009. An update of the Angiosperm Phylogeny Group classification for the orders and families of flowering plants: APG III. Botanical Journal of the Linnean Society161: 128-131) has resulted in the need for a revised systematic listing of the accepted families. This linear APG III (LAPG III) sequence of families is presented here.